1,6-Conjugate addition of in situ generated aryldiazenes to p-quinone methides - Mamale, Ajay G.; Paul, Sayantan; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2024)
Herein we report a transition-metal free, base-mediated 1,6-conjugate addition of aryldiazenes to para-quinone methides (p-QMs). Arylhydrazines were used for the in situ generation of aryldiazenes using a base-mediated protocol in the presence of air as the oxidant. The 1,6-conjugate addition of aryldiazenes to para-quinone methides via a radical mechanism is followed by an oxidative rearrangement to furnish the desired product, arylhydrazones. Interestingly, our synthetic protocol results in the formation of an aryldiazene radical, which undergoes 1,6-conjugate addition with p-QMs to furnish the arylhydrazones.